1970
DOI: 10.3329/taj.v21i2.3788
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Report on Non-adherence to Antihypertensive Treatment in Essential Hypertensive Patients: A Community Based Survey

Abstract: A cross-sectional study was conducted on 300 hypertensive patients living in urban and rural community in Rajshahi District of Bangladesh to assess the situation regarding antihypertensive drug non-adherence. Patients aged 35 years or above who are taking antihypertensive drug for at least 6 months were included in the study. About 87% of patients were found non-adherent to treatment. The non-adherent patients had missed taking medication for anywhere from one day to the whole month. The reasons for not taking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…That result was approximately similar to Ekram et al study; they reported that 70% were poor and earning < 10,000 taka per month 18 reflecting hypertension is not a disease of rich. Duration of disease has a great negative impact onadherence as it may bore the patient and promote non-adherence.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…That result was approximately similar to Ekram et al study; they reported that 70% were poor and earning < 10,000 taka per month 18 reflecting hypertension is not a disease of rich. Duration of disease has a great negative impact onadherence as it may bore the patient and promote non-adherence.…”
Section: Discussionsupporting
confidence: 80%
“…Most of the respondents had a poor knowledge of the sideeffects of antihypertensive as reported by Ekramet al 18 .Most of the (87.5%) participant went for follow up when they felt hypertensive, 94%of them missed their follow up in their course of illness, 35% changed medicine for expenses and 27% stop taking drug when BP is under control which indicates poor knowledge on adherence. Regarding perception, about 63% patients felt hypertension is not a curable disease, 77.4% of the respondent said that preservation of previous prescription is important to understand HTN status.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…52 In another study conducted in Bangladesh, forgetfulness, busy schedule and boredom were reported as the three main factors for medication non-adherence in hypertensive patients. 53 All of these South Asian studies showed that forgetfulness, feeling well/no need for medicines were the major reasons for medication non-adherence in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%